Design of Digital Workplace Stress-Reduction Intervention Systems: Effects of Intervention Type and Timing - Howe, Esther; Suh, Jina; Morshed, Mehrab Bin; McDuff, Daniel; Rowan, Kael; Hernandez, Javier; Abdin, Marah Ihab; Ramos, Gonzalo; Tran, Tracy; Czerwinski, Mary (CHI 2022, 2022)
Workplace stress-reduction interventions have produced mixed results due to engagement and adherence barriers. Leveraging technology to integrate such interventions into the workday may address these barriers and help mitigate the mental, physical, and monetary effects of workplace stress. To inform the design of a workplace stress-reduction intervention system, we conducted a four-week longitudinal study with 86 participants, examining the effects of intervention type and timing on usage, stress reduction impact, and user preferences. We compared three intervention types and two delivery timing conditions: Pre-scheduled (PS) by users and Just-in-time (JIT) prompted by the system-identified user stress-levels. We found JIT participants completed significantly more interventions than PS participants, but post-intervention and study-long stress reduction was not significantly different between conditions. Participants rated low-effort interventions highest, but high-effort interventions reduced the most stress. Participants felt JIT provided accountability but desired partial agency over timing. We present type and timing implications.